MODERN CHALLENGES AND PROSPECTS FOR THE DEVELOPMENT OF PERI-URBAN AGRICULTURE IN SAMARKAND CITY OUTSKIRTS - Ibragimov, Lutfullo Ziyadullayevich; Berdikulov, Firdavs Farxod ugli (SCIENCE and SOCIETY, 2026)
The article analyzes the issues of sustainable development of peri-urban agriculture around Samarkand city. Under conditions of urbanization and population growth increasing pressure on food systems, the importance of rational land use, modern irrigation methods, and the introduction of advanced agrotechnologies is substantiated. Peri-urban agricultural areas are considered a strategic system for ensuring food security.